Clinical Outcomes Used in Clinical Pharmacy Intervention Studies in Secondary Care - Lene Juel Kjeldsen; Charlotte Olesen; Merete Kjær Hansen; Trine Rune Høgh Nielsen (MDPI AG, 2017)
The objective was to investigate type, frequency and result of clinical outcomes used in studies to assess the effect of clinical pharmacy interventions in inpatient care. The literature search using Pubmed.gov was performed for the period up to 2013 using the search phrases: "Intervention(s)" and "pharmacist(s)" and "controlled" and "outcome(s)" or "effect(s)". Primary research studies in English of controlled, clinical pharmacy intervention studies, including outcome evaluation, were selected. Titles, abstracts and full-text papers were assessed individually by two reviewers, and inclusion was determined by consensus. In total, 37 publications were included in the review. The publications presented similar intervention elements but differed in study design. A large variety of outcome measures (135) had been used to evaluate the effect of the interventions; most frequently clinical measures/assessments by physician and health care service use. No apparent pattern was established among primary outcome measures with significant effect in favour of the intervention, but positive effect was most frequently related to studies that included power calculations and sufficient inclusion of patients (73% vs. 25%). This review emphasizes the importance of considering the relevance of outcomes selected to assess clinical pharmacy interventions and the importance of conducting a proper power calculation.